(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the issue of interference of phraseological units in Korean and Uzbek languages. Phraseological units are an integral part of language and culture, and their translation and mutual influence often give rise to numerous linguistic and cultural challenges. The study compares phraseologisms in both languages, analyzing their structure, meaning, and similarities and differences in cultural context. Furthermore, the article explores how interference manifests in language learning and translation. The findings highlight the importance of an intercultural approach in studying phraseological units.